-13-(-4)=

Simple and best practice solution for -13-(-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-(-4)= equation:


-13-(-4)=0

We simplify the equation to the form, which is simple to understand
-13-(-4)=0

Remove unnecessary parentheses
-13+4=0

We move all terms containing to the left and all other terms to the right.
0=0+13-4

We simplify left and right side of the equation.
0=+9

0=9

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| -8x-19=5y | | 5+6(X+2)=7+8X | | inx+inx(x-3)=0 | | 4y+4y+3=15 | | 5x-9=6x-15 | | 2*log(x)-log(9)=log(441) | | 2+6x=-5y | | m^2-12m+36=7 | | m^2-12m+29=0 | | 6+2(X+1)=8+2X | | 4x-2y=5y | | -27y=-24x+24 | | h(x)=20000(1.12) | | 16z^2-24z-90=0 | | 5x+y=-z | | 20v*v+44v+-15=0 | | 3y=3x+0 | | 8x-1=47 | | y=8cos(4x) | | -5.4f+4.4-(2f+0.4)+2.9f= | | 2x+6-x= | | 56=17p-(-26) | | -6z-18=132 | | 4y=12x-4 | | 9x^2-48x=0 | | (3x-5)=(2x+10) | | 7(3n-3)=5-4n | | X+3.7=7.5 | | log(8)(x+4)+log(8)(x+6)=log(8)24 | | 6(w+5)=5w-4 | | 5x^2+14x-15=0 | | 48=10x^2-28x |

Equations solver categories